Quantitation of large, middle and small hepatitis B surface proteins in HBeAg‐positive patients treated with peginterferon alfa‐2a. (18th December 2019) - Rinker, Franziska; Bremer, Corinna M.; Schröder, Kathrin; Wiegand, Steffen B.; Bremer, Birgit; Manns, Michael P.; Kraft, Anke R.; Wedemeyer, Heiner; Yang, Lei; Pavlovic, Vedran; Wat, Cynthia; Gerlich, Wolfram H.; et al.
Abstract: Background & Aims: Hepatitis B virus (HBV) contains three viral surface proteins, large, middle and small hepatitis B surface protein (LHBs, MHBs, SHBs). Proportions of LHBs and MHBs are lower in patients with inactive vs active chronic infection. Interferon alfa may convert hepatitis B e antigen (HBeAg)‐positive chronic hepatitis B (CHB) to an inactive carrier state, but prediction of sustained response is unsatisfactory. The aim of this study was to test the hypothesis that quantification of MHBs and LHBs may allow for a better prognosis of therapeutic response than total hepatitis B surface antigen (HBsAg) concentration. Methods: Hepatitis B surface proteins were measured before and during peginterferon alfa‐2a therapy in serum from 127 Asian patients with HBeAg‐positive CHB. Sustained response was defined as HBeAg seroconversion 24 weeks post‐treatment. Results: Mean total HBs levels were significantly lower in responders vs nonresponders at all time points ( P < .05) and decreased steadily during the initial 24 weeks treatment (by 1.16 vs 0.86 ng/mL in responders/nonresponders respectively) with unchanged relative proportions. Genotype B had a two‐fold higher proportion of LHBs than genotype C (13% vs 6%). HBV DNA, HBeAg, HBsAg and HBs protein levels predicted response equally well but not optimally (area under the receiver operating characteristic curve values >0.70). Conclusions: Hepatitis B surface protein levels differ by HBV genotype. However, quantification of HBs proteins has no advantage over the already established HBsAg assays to predict response to peginterferon alfa‐2a therapy in HBeAg‐positive patients.